28 GHz balanced pHEMT VCO with low phase noise and high output power performance for 5G mm-Wave systems - Abdelhafid Es-saqy; Maryam Abata; Mahmoud Mehdi; Said Mazer; Mohammed Fattah; Moulhime El Bekkali; Catherine Algani (International Journal of Electrical and Computer Engineering (IJECE), 2020)
This paper presents the study and design of a balanced voltage controlled oscillator VCO for 5G wireless communication systems. This circuit is designed in monolithic microwave integrated circuit (MMIC) technology using PH15 process from UMS foundry. The VCO ensures an adequate tuning range by a single-ended pHEMT varactors configuration. The simulation results show that this circuit delivers a sinusoidal signal of output power around 9 dBm with a second harmonic rejection between 25.87 and 33.83 dB, the oscillation frequency varies between 26.46 and 28.90 GHz, the phase noise is -113.155 and -133.167 dBc/Hz respectively at 1 MHz and 10 MHz offset and the Figure of Merit is -181.06 dBc/Hz. The power consumed by the VCO is 122 mW. The oscillator layout with bias and RF output pads occupies an area of 0.515 mm2.